A new genus and species of soldier beetle from Upper Cretaceous Burmese amber (Coleoptera, Cantharidae, Malthininae). (January 2017) - Hsiao, Yun; Ślipiński, Adam; Deng, Congshuang; Pang, Hong
Abstract: A new Upper Cretaceous genus and species of soldier beetles, Archaeomalthodes rosetta gen. et sp. nov., is described and illustrated from an individual preserved in Upper Cretaceous (Cenomanian, ca. 99 Ma) amber from northern Myanmar. It is undoubtedly placed in extant subfamily Malthininae based on its small-sized body, somewhat abbreviated elytra and fusiform terminal maxillary palpomere, representing the oldest documented occurrence of Malthininae. It suggests that this subfamily is an ancient group, which originated at least in the earliest Late Cretaceous. Our discovery sheds light on the palaeodiversity of Cantharidae in the Late Mesozoic. Together with other previously reported fossil cantharids, it is likely that Malthininae has been fairly diverse during the early evolution of Cantharidae. On the other hand, a morphological similarity between Archaeomalthodes and Recent malthinines and the occurrence of flowering plants in the Burmese amber implies a potential flower-visiting behaviour of this fossil species.